MODERASI UKURAN PERUSAHAAN PADA KUALITAS AUDIT DAN USIA PERUSAHAAN TERHADAP MODAL EKUITAS - Rivera, Lidwina Nurilhaq; Naimah, Zahroh (Program Studi Akuntansi FPEB UPI, 2021)
The cost of equity capital relates to the risk of investing in company shares. The purpose of this study was to analyze the effect of audit quality and company age on the cost of equity capital moderated by company size. The sample in this study were manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2018 period. Data collection in this study was carried out by literature and documentation. The analysis technique in this research is Partial Least Square (PLS) analysis. The results in this study prove that audit quality has a significant effect on the cost of equity capital while company age does not have a significant effect on the cost of equity capital as well as audit quality does not have a significant effect on the cost of equity capital as moderated by company age.